(untitled) (Research, Society and Development, 2022)
Covid-19 is an infectious disease caused by the Coronavirus (CoV), responsible for severe acute respiratory syndrome (SARS-CoV-2), and a wide variety of clinical manifestations, including those related to the involvement of the inner ear. This study is an Integrative Literature Review (ILR) that used DeCS descriptors and the VHL, LILACS and MEDLINE databases. This search initially resulted in x articles, and after applying exclusion and inclusion criteria, x remained, which were considered suitable for the final sample. The most frequent symptoms related to the inner ear were: tinnitus, vertigo and hearing loss. Most of the symptoms were self-limited, appearing in the acute phase of the disease with subsequent remission. Patients with previous diagnoses of ear pathologies stood out, as they had a greater variety of otological symptoms when compared to previously healthy patients. However, further studies are still needed relating covid 19 and ear involvement, since there are still few studies on the pathophysiology and mechanisms of injury involved in the genesis of these symptoms, although several hypotheses have already been raised.